Project Aid and Firm Performance - Silvia Marchesi; Tania Masi; Saumik Paul (Institute of Labor Economics (IZA), 2021)
This paper evaluates the effect of development project aid from the World Bank and China on firms' sales growth, using a large dataset of 110864 firms spanning 121 countries between 2001 and 2016. We find that, contrary to the World Bank, Chinese ODA projects increase, on average, firm sales and, compared to sector-specific, Chinese region-specific aid positively affect firm performance. Finally, we show that the positive effect of Chinese aid is stronger for firms lacking transport infrastructure (and with better electricity provision), suggesting that aid may improve firm performance by releasing their infrastructure constraints.
Keywords: F35; O19; D22; 330; aid effectiveness; world bank projects; chinese projects; geo-coding; firm growth